1983
DOI: 10.1111/j.1600-0447.1983.tb00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent discrepancy in international diagnostic practice since 1970

Abstract: National admission statistics by diagnosis since 1970, were available from seven WHO member countries. All had officially introduced the ICD 8, but only two countries strictly adhered to the ICD categories in practice. The new 3-digit category 298 (Other psychosis) has met with no success, nor did the new subgroups of schizophrenia with a favourable outcome (295.4, 295.5 and 295.7) gain much acceptance. The discrepancy in diagnostic distribution is virtually unchanged from that before 1970 with a persistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
(7 reference statements)
1
12
0
Order By: Relevance
“…However, as we all know, this is not the case for schizophre nia and manic-depressive psychosis [16]. The prevalence of reactive psychoses also varies widely in the official statistics of the countries which have a tradition with this concept [4], We therefore have a problem of cultural differences in the prevalence of reac tive psychoses. However, as demonstrated in Scandinavia, there are considerable differ ences in prevalence between neighboring countries, which are quite close in language and culture.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…However, as we all know, this is not the case for schizophre nia and manic-depressive psychosis [16]. The prevalence of reactive psychoses also varies widely in the official statistics of the countries which have a tradition with this concept [4], We therefore have a problem of cultural differences in the prevalence of reac tive psychoses. However, as demonstrated in Scandinavia, there are considerable differ ences in prevalence between neighboring countries, which are quite close in language and culture.…”
Section: Prevalencementioning
confidence: 99%
“…The term 'reactive psychosis' was strongly endorsed internationally by the Norwegian psychiatrist 0degard [4]. The term was meant by him to cover the functional psy choses which were not of clearly schizo phrenic, manic-depressive or paranoid type.…”
Section: Information and Terminologymentioning
confidence: 99%
“…On the other hand, when the reactive psychoses are taken as criterion diagnoses, it turns out that nearly half of these cases get a diagnosis within the schizophrenia spectrum in DSM-111. It has been shown that 35% of the Norwegian cases that get a diagnosis of reactive psychosis at first admission, will later get a diagnosis of schizophrenia (2). One can therefore assume that some of the cases with a diagnosis of reactive psychosis in ICD-8 that get a diagnosis within the schizophrenic/schizophreniform disorders in DSM-111, later will get a diagnosis of schizophrenic psychosis in ICD-8 too.…”
Section: Discussionmentioning
confidence: 99%
“…The concept is similar in all countries. There was a 50% increase in first admissions classified as manic depression in Norway during 1926Á65 (Saugstad and Ødegård 1980(Saugstad and Ødegård , 1983(Saugstad and Ødegård , 1987. This increase occurred almost entirely after 1955, when a growing proportion was classified as ''non-psychotic'', while a great number of these non-psychotic depressions were involuntarily admitted as being considered psychotic.…”
Section: High Familial Loading Low Standard Of Living and Schizophreniamentioning
confidence: 95%
“…This became the most used psychiatric diagnosis in subsequent years (Ødegård 1971, 40% in 1965). Denmark also introduced a third category of functional psychosis: psychogenic psychosis, which became a similarly popular diagnosis (Saugstad and Ødegård 1980(Saugstad and Ødegård , 1983(Saugstad and Ødegård , 1985.…”
Section: Warning Signs and Symptomsmentioning
confidence: 99%